2008
DOI: 10.4040/jkan.2008.38.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nursing Key Performance Indicators for an Intensive Care Unit by using a Balanced Scorecard

Abstract: Purpose:The purpose of this study was to develop visions of nursing service, nursing strategies and key performance indicators (KPIs) for an intensive care unit (ICU) based on a Balanced Scorecard (BSC). Methods: This study was undertaken by using methodological research. The development process consisted of four phases; the first phase was to develop the vision of nursing in ICUs. The second phase was to develop strategies according to 4 perspectives of a BSC. The third phase was to develop KPIs according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Even though a number of additional studies from European countries (Isfort, 2013) and Korea (Choi et al, 2008) were identified in the search, those were not published in the English language, and were thus excluded. To the authors' knowledge, the AIRE instrument has not been used previously in the context of assessing QIs in the ICU.…”
Section: Limitationsmentioning
confidence: 99%
“…Even though a number of additional studies from European countries (Isfort, 2013) and Korea (Choi et al, 2008) were identified in the search, those were not published in the English language, and were thus excluded. To the authors' knowledge, the AIRE instrument has not been used previously in the context of assessing QIs in the ICU.…”
Section: Limitationsmentioning
confidence: 99%
“…The area covered per bed is 367.992 square foot. Figure 5 & 6 represent the two nurse station relationship, and the photo taken by author on eye level along with the space syntax analysis of eye level, Choi, Y. J [39]. The logWare simulation provided the minimum distance covered by the nurse from both the station.…”
Section: Case Studymentioning
confidence: 99%
“…Space Syntax. Healthcare trends research for this article has groomed to be more interactive and participatory, often combined with author"s insight research and innovation design activities to make better sense of complex trends [19].…”
Section: Case Study Icu Plan Typementioning
confidence: 99%